5PSQ-098 Allergies and intolerances: an opportunity for improvement. (24th March 2020) - Ibáñez Zurriaga, MD; Ruiz Garcia, S; Ramírez Herraiz, E; Garcia Peralo, A; Cidoncha Muñoz, I; Calvo Garcia, A; Ramos Martinez, B; Perez Abanades, M; Morell Baladron, A
Abstract : Background and importance: In 2014, the Institute of Safe Medication Practice published a bulletin that showed the importance of drug hypersensitivity reactions. Pharmacy services could contribute to identify and avoid allergic reactions in patients. Aim and objectives: To evaluate the allergies and intolerances register system, the level of acceptance of pharmaceutical interventions and to determinate the most frequent pharmacological groups that cause allergies. Material and methods: A prospective study was conducted of allergies and intolerances registered in the medical history and prescription programme in a cohort of inpatients during the study period. Phase 1 (October 2018) was observational and included a situation analysis, except for a safety intervention if the patient was at risk. During phase 2 (November–December 2018), allergies/intolerances registered only in the medical history were identified and pharmacists informed the prescribers. Results: Phase 1 included 374 patients, 60 (16%) with some allergy. In total, 71 allergies were described in the medical history but only 27% appeared in the prescription programme. A drug with allergy known was prescribed in 4 patients. Phase 2 included 1039 patients, 136 (13%) with allergies and 32 (3%) with intolerances. Of 232 allergies and 41 intolerances described, only 37% and 7%, respectively, were registered in the prescription programme. Drugs with allergies or intolerances prescribed were found in 7 and 3 patients, respectively. After pharmacist interventions, only 23% were approved and registered by the physician. Medical services registered 31% of allergies versus 49% in the surgical services. Anti-infectives and CNS drugs reached 66% of the total allergies. Conclusion and relevance: Most interventions (77%) were not accepted and not registered in the prescription programme. Surgical services registered more allergies than medical services. Drug administration was avoid in 11 patients with allergies due to pharmacist intervention. Anti-infectives and CNS drugs were the groups involved more frequently in allergies. Promotion of the allergies/intolerances register is needed to avoid erroneous administration in allergic patients. References and/or acknowledgements: No conflict of interest.